“It’s a bit exasperating to be locked up”- an exploration of Mexican adolescents’ perceived barriers and facilitators for physical activity and healthy eating - Gabriela Argumedo; Martyn Standage; Thomas Curran; Fiona Gillison (Revista Brasileira de Atividade Física e Saúde)
Mexican adolescents’ diet and physical activity levels fall short of recommendations for health. The aim of this study was to explore Mexican adolescents’ perceived barriers and facilitators of physical activity and healthy eating. Twelve single-sex focus groups were conducted in six secondary schools in Mexico City during three months from October 2016. Data were analysed via inductive thematic analysis. Three themes were identified, namely: understanding the health-behaviour link, the impact of a restricted life, and social support. Participants understood how physical activity contributes to multiple dimensions of health, and how diet contributes to physical health. They also identified socialising, having fun, and stress relief as facilitators of physical activity, and knowledge and the desire for healthy food as facilitators for healthy eating. Barriers included inadequate facilities, insufficient time within current school structures, and inadequate social support from teachers. Context-specific physical activity barriers of neighbourhood safety concerns, and limited family support were also reported. Participants had a basic knowledge of healthy eating but showed little motivation to improve their diet. In conclusion, the findings of this study suggest that improvement of opportunities for safe outdoor time, social support, and availability of healthy food would be useful to explore to promote the health behaviours of Mexican adolescents.